2023
DOI: 10.1186/s12884-022-05304-8
|View full text |Cite
|
Sign up to set email alerts
|

Reducing preventable adverse events in obstetrics by improving interprofessional communication skills – Results of an intervention study

Abstract: Background Progress in medicine involves the structured analysis and communication of errors. Comparability between the individual disciplines is only possible to a limited extent and obstetrics plays a special role: the expectation of a self-determined and joyful event meets with possibly serious complications in highly complex care situations. This must be managed by an interdisciplinary team with an increasingly condensed workload. Adverse events cannot be completely controlled. However, tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…If women lack this experience of giving birth in a "natural" (and often socially idealized) way, they may blame themselves for not making it and feel feelings of failure or guilt [39], which in turn is associated with higher depression scores. This is supported by the ndings of a recent German study [40], which showed that women without a natural childbirth are more likely to suffer from feelings of guilt and higher depressive symptomatology. Following on from this it seems explainable, that although AVD is associated with worse delivery experiences [41], women had no elevated depression levels.…”
Section: Discussionmentioning
confidence: 57%
“…If women lack this experience of giving birth in a "natural" (and often socially idealized) way, they may blame themselves for not making it and feel feelings of failure or guilt [39], which in turn is associated with higher depression scores. This is supported by the ndings of a recent German study [40], which showed that women without a natural childbirth are more likely to suffer from feelings of guilt and higher depressive symptomatology. Following on from this it seems explainable, that although AVD is associated with worse delivery experiences [41], women had no elevated depression levels.…”
Section: Discussionmentioning
confidence: 57%
“…40 Shared mental models are enhanced through education, support a positive team environment, and reduce adverse patient outcomes. 41 The focus of both nurse and physician participants on nurse-initiated patient care communication in this study highlighted the importance of nurses' understanding of significant changes in patient status during decision making and communication of these changes with physicians. Physicians in this study valued effective nurse communication to support their understanding of patient status when making patient care decisions.…”
Section: Discussionmentioning
confidence: 95%
“…Other research results indicate that well-designed teams similarly develop an understanding of each team member's skills, well-defined roles, team education, and mutual respect 40 . Shared mental models are enhanced through education, support a positive team environment, and reduce adverse patient outcomes 41 …”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous healthcare settings, obstetrics units are areas of care that particularly account for a significant amount of complaints [ 4 , 5 ]. They present a significant risk of morbidity and mortality for both mothers and fetus, requiring an effective safety environment to avoid negative outcomes [ 4 , 5 ]. Providing obstetric care involves several interrelated factors making it at a higher risk of errors than other specialties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%